Analisis Aksesibilitas Website Pemerintah Provinsi Indonesia Sebagai Implementasi Corporate Digital Responsibility terhadap E-Government - Amaliah, St. Mukhlisahtul; Hafiar, Hanny; Dewi, Retasari (Prologia, 2023)
The rapid development of ICT raises risks that can occur, such as the accessibility of digital information by persons with disabilities. Accessibility is an aspect of equality that has been recognized by Indonesia, particularly access to information and public services such as the government website. However, previous findings show that government websites in various countries do not have good accessibility. It requires an understanding of corporate digital responsibility in managing government websites so that accessibility can be implemented effectively. This research is conducted to analyze the accessibility of Indonesian provincial government websites as a form of CDR implementation for e-government. This study uses a quantitative content analysis method, by utilizing aXe DevTools as an automatic accessibility evaluation tool to collect data from 34 provincial government websites. The accessibility standard used in analyzing websites is WCAG 2.1 by W3C. This research found that the 34 provincial government websites had a total of 2,088 accessibility violations with 24 types of accessibility errors categorized into 3 accessibility issues category. These violations were found to greatly affect persons with disabilities, with different needs and abilities, in accessing public information on the provincial government website. A review of website management needs to be carried out to ensure that information on the website can be accessed by all levels of society. Apart from that, the role of government public relations practitioners also needs to be emphasized again to ensure that all information in government communication activities can be accessed by all levels of society, especially people with disabilities. Pesatnya perkembangan TIK dapat menimbulkan risiko seperti aksesibilitas informasi digital oleh penyandang disabilitas. Aksesibilitas merupakan aspek kesetaraan yang telah diakui oleh Indonesia, termasuk akses terhadap informasi dan layanan publik seperti website pemerintah. Namun ditemukan bahwa website pemerintah dari berbagai negara tidak memiliki aksesibilitas yang baik. Diperlukan adanya pemahaman tentang corporate digital responsibility dalam mengelola website pemerintah agar aksesibilitas dapat diterapkan secara efektif. Penelitian ini bertujuan untuk menganalisis aksesibilitas website pemerintah provinsi Indonesia sebagai bentuk implementasi CDR terhadap e-government. Penelitian ini menggunakan metode analisis isi kuantitatif, dengan memanfaatkan axe DevTools sebagai alat evaluasi aksesibilitas otomatis untuk mengumpulkan data dari 34 websitepemerintah provinsi. Acuan standar aksesibilitas yang digunakan adalah WCAG 2.1 by W3C. Penelitian ini menemukan bahwa 34 website pemerintah provinsi memiliki total 2.088 pelanggaran aksesibilitas dengan 24 jenis error yang dikategorikan ke dalam 3 kategori issues. Pelanggaran tersebut mempengaruhi penyandang disabilitas, dengan kebutuhan dan kemampuan yang berbeda, dalam mengakses informasi publik pada website pemerintah provinsi. Peninjauan ulang pengelolaan website perlu dilakukan untuk memastikan kembali informasi pada website dapat diakses oleh seluruh kalangan masyarakat. Selain itu, peran praktisi humas pemerintah juga perlu ditekankan kembali untuk memastikan setiap informasi dalam aktivitas komunikasi pemerintah dapat terakses oleh semua kalangan masyarakat, khususnya penyandang disabilitas.